Virtual Reality in Medicine - Kaltenborn, K.-F.; Rienhoff, O. (Methods of Information in Medicine, 1993)
Virtual reality (VR), as part of computer science, allows computer-based models of the real world to be generated, and provides humans with a means to interact with these models through new human-computer interfaces and, thus, to nearly realistically experience these models. This contribution explores the technical requirements for VR, describes technological advances and deficits, and analyzes the framework for future technological research and development. Although some non-medical applications are discussed, this contribution focuses primarily on medical applications of VR and outlines future prospects of medical VR applications. Finally, possible hazards arising from the use of VR are discussed. The authors recommend an interdisciplinary approach to technology assessment of VR.
Keywords: Virtual Reality; Human-Computer Interface; Human-Computer Communication